2021
DOI: 10.1177/00333549211042577
|View full text |Cite
|
Sign up to set email alerts
|

Rapid Development, Training, and Implementation of a Remote Health Profession’s Student Volunteer Corps During the COVID-19 Pandemic

Abstract: Public health in the United States has long been challenged by budget cuts and a declining workforce. The COVID-19 pandemic exposed the vulnerabilities left by years of neglecting this crucial frontline defense against emerging infectious diseases. In the early days of the pandemic, the University of Texas Medical Branch and the Galveston County Health District (GCHD) partnered to bolster Galveston County’s public health response. We mobilized interprofessional teams of students and provided training to implem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 9 publications
0
8
0
Order By: Relevance
“…Additionally, medical students are usually consulted for healthcare suggestions and biochemical report analysis from their known relations. This is because they tend to have a better knowledge than students of allied science branches when the health management issues [4,6] are considered. It is a known fact that this knowledge is more in medical students in their later stages of studies [7].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Additionally, medical students are usually consulted for healthcare suggestions and biochemical report analysis from their known relations. This is because they tend to have a better knowledge than students of allied science branches when the health management issues [4,6] are considered. It is a known fact that this knowledge is more in medical students in their later stages of studies [7].…”
Section: Discussionmentioning
confidence: 99%
“…The COVID-19 pandemic due to the SARS-CoV-2 virus had its inception in Wuhan, China in December 2019, probably as a result of crossspecies transmission [1] affecting practically every country on the planet, causing largely moderate symptoms of the respiratory tract in which the majority was an infection of the upper portion of the tract [2,3] The reason why some people become seriously ill while others do not is still a mystery. For risk stratification, comorbidities and laboratory indicators have been proposed [4,5].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A study regarding volunteer corps during the COVID-19 pandemic indicated that the flexibility of remote opportunities allowed volunteers' involvement in services. They may otherwise have been unable to participate due to personal or financial constraints ( 26 ). The government departments advocated making full use of the information platform to achieve the aim of systematic management of volunteer registration and recruitment in the service preparation stage.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, some countries used volunteers and students to cope with staff shortfalls. Many volunteers from government, clinical, public health, and non-medical areas were recruited to deal with COVID-19 surges [11,16,18,28,[46][47][48][49][50]. For example, Malaysia utilized volunteers from non-healthcare ministries, government agencies, and NGOs.…”
Section: Recruiting Volunteers/fast-tracking Medical Studentsmentioning
confidence: 99%